PENGARUH KEPERCAYAAN MEREK DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS MEREK MITSUBISHI XPANDER PADA PT. MAKASSAR MANDIRI PUTRA UTAMA - Adhitya Al Qadri; Nursaban Rommy; Sinarwaty Sinarwaty; Hayat Yusuf; Nurul Ittaqullah (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2023)
This study aims to determine the effect of brand trust and consumer satisfaction on brand loyalty Mitsubishi Xpander at PT. Makassar Mandiri Putra Utama. The population in this study were all consumers at PT. Makassar Mandiri Putra Utama meanwhile, the sample is 30 samples. Data analysis was performed using multiple linear regression analysis techniques. The results showed that brand trust and consumer goals had a positive and significant effect on brand loyalty on Mitsubishi Xpander at PT. Makassar Mandiri Putra Utama